Strategic SWOT analysis of the University of Nigeria Teaching Hospital using Modified Delphi Technique: implications for strengthening national and regional health systems - Cyril Chukwudi Dim; Chinyere Ojiugo Mbachu; Nympha Onyinye Enebe; Wilson Chukwukasi Kassy; Johnpaul Ejikeme Nnagbo; Ikechukwu Emmanuel Obi; Nkiruka Pauline Onodugo; Nwamaka Ngozika Lasebikan; Obinna Donatus Onodugo (BMC Health Services Research)
Abstract Background and aim The perennial underperformance of the Nigerian Health System necessitated enhanced advocacy for health to be placed at the centre of a renewed social contract and as a means of bolstering public trust. The hospital management of the University of Nigeria Teaching Hospital (UNTH) introduced initiatives to improve the hospital’s operational environment and service performance in response to the population served. Following these changes, an Organizational Capacity Assessment (OCA) is critical to direct further development in the organization. Methods A comprehensive Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was conducted for the UNTH across twelve broad areas. The Modified Delphi Technique was adopted for the identification and prioritization of the organizational SWOTs. Thirty key stakeholders and leaders in the organization were first consulted to identify the SWOTs. This was followed by a structured ranking of the SWOTs by 109 staff of UNTH to isolate the priority assets and needs of the organization. Results The top strengths were mainly related to the hospital's resources like its large expanse of land, staff capabilities like their skills and training, as well as their prevailing language, and existing hospital partnerships. The identified weaknesses were associated with challenges such as transportation for staff to work, infrastructure (lack of staff accommodation and office space), and health workforce shortages due to migration. The highest ranked opportunity was in the Epidemiology and Disease Surveillance broad area while the highest ranked threat was in the leadership and governance broad area. Conclusion This SWOT analysis has highlighted the strategic aspects of UNTH's operations. By identifying its internal strengths and weaknesses and external opportunities and threats, the hospital can thus formulate effective strategies to enhance its performance and maintain its position as a leading healthcare institution.